Conservation linkages of rare and endangered medicinal plants used in the traditional health care system in Pin Valley National Park, Himachal Pradesh - Targe, Kalzang; Lyngdoh, Salvador; Bussmann, Rainer W.; Adhikari, Bhupendra Singh (Ethnobotany Research and Applications, 2022)
Background: The Amchi system ‘Sowa-Rigpa’ served as the cornerstone of local healthcare system for many years, but now is on the verge of extinction. Therefore, to maintain the long-term survival of this system, it is necessary to document utilization of medicinal plants, treatments performed, status of plants, their habitats and factors influencing the decline of this system. Methods: A systematic field survey was performed from May 2019 to January 2020 covering all 13 villages (2270 souls in 545 households) with 12 Amchies in Pin Valley. Amchies practicing Sowa-Rigpa system were interviewed using semi-structured questionnaires. Knowledge Richness Index (KRI) and the Use Value (UV) were calculated to measure the knowledge on medicinal plants and the significance of the species, respectively. The vegetation sampling was performed by laying 25, 1x1m quadrats in each habitat during the peak growing season. The Pearson’s correlation and Mann-Whitney U test were performed using Past 4.03 to analyze the knowledge among different age classes and different professions among practitioners. Results: Forty-seven endangered plant species were used to treat 27 different ailments. The most common ailment was osteoarthritis (12%), while the decline in Amchi population was 45% in last few decades. Amchies involved in government services, as well as farming, observed high knowledge as compared to others. Three critical habitats for critically threatened medicinal plants were identified in the buffer zone. People highly referred to the allopathic system (63%) followed by Amchi system (17%) and for both 20%. Conclusions: The lack of income, government incentives and enthusiasm among younger generation in practicing this system may jeopardize Sowa-Rigpas’ survival. Integration of this system with modern healthcare system, as well as additional government job possibilities and women’s involvement may be effective to enhance this diminishing tradition. Keywords: Amchi, Trans-Himalaya, Medicinal plants, Spiti Valley, Sowa-rigpa